The application of visual metaphor in designing environment for short animation Lost Steps - Gho, Jessica Meriani; Kusumawardhani, Mega Iranti (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
Animation as an art medium comprises many important elements, including the environment. The environment is used to visualize the condition, background, time, location, culture, mood, and atmosphere of certain aspects of animation. Environment design is crucial in creating ‘realistic’ animation; realistic in terms that it is believable through the viewer’s perspective. This article aims to explain the design process of environmental aspects in the “Lost Steps” short animation. “Lost Steps” tells the story of Rahel, a grieving young woman, who lost her steps in the painting world because of her grandmother’s death. This movie focuses on how Rahel goes through her grief to release the emotional baggage that’s eating into her life. The purpose of this paper is to elucidate the importance of good interior environment design in order to convey emotions through visuals. In order to explain all of these, the writer decided to use an embodied visual metaphor. This paper uses qualitative analysis techniques in its writing to discuss the environmental aspects of the movie. The result achieved through this paper is that visual metaphor is used in terms of creating layers of meaning, while mise-en-scène is applied through the use of property set, asset design, color, and lighting to visualize these layers of meaning.